Cover Image. (11th July 2018) - Steger, Klaus; Balhorn, Rod
Abstract : The cover image, by Klaus Steger, Rod Balhorn, is based on the Invited Review Sperm nuclear protamines: a checkpoint to control sperm chromatin quality, DOI:10.1111/ahe.12361 . Design Credit: Alexander Kruse and Dr. Constanze Maresch.